Fault-tolerant leader-following consensus for multi-agent systems subject to semi-Markov switching topologies: An event-triggered control scheme. (November 2019) - Shen, Hao; Wang, Yuan; Xia, Jianwei; Park, Ju H.; Wang, Zhen
Abstract: For multi-agent systems with switching topologies, the work addresses the fault-tolerant leader-following consensus issue. A semi-Markov chain is applied to describe randomly topological switching which may be caused by the complexity of network communication. In addition, in order to improve the utilization of bandwidth and relieve the burden of the communication channels in the multi-agent networks, a fault-tolerant event-triggered control protocol is developed to obtain the leader-following consensus of the multi-agent systems. By constructing an appropriate Lyapunov–Krasovskii functional and using some novel inequalities, the sufficient conditions of leader-following consensus are derived. One numerical simulation example validates the effectiveness of the presented method at length.